Exploring the cybercrime capacity and capability of local law enforcement agencies in the United States - Moloney, Christopher Jerome, author; Unnithan, N. Prabha, advisor; Lacy, Michael G., committee member; Mao, KuoRay, committee member; MacDonald, Bradley, committee member (Colorado State University. Libraries, 2021)
The relentless pace of technological innovation has changed how people communicate, interact, and conduct business, creating new pathways and opportunities for people to commit crimes or engage in harmful behavior via the internet or digitally networked devices. Cybercrime is rapidly scaling up, leading many to predict that it will become the next significant global crisis (Krebs, 2021; Viswanathan & Volz, 2021; Zakaria, 2021). In the United States, local law enforcement agencies and their personnel stand at the frontlines of the cybercrime problem (Police Executive Research Forum, 2014). This dissertation project was inspired by several calls to action to explore and evaluate how law enforcement agencies are responding to the cybercrime problem (Holt & Bossler, 2014; Ngo & Jaishankar, 2017). The research conducted in this project aligns with and extends a small body of exploratory and evaluative research focusing on local law enforcement agencies and cybercrime (for example Harkin et al., 2018; Monaghan, 2020; Nowacki & Willits, 2016). By utilizing a mixed methods research design consisting of a survey and series of qualitative interviews this project helped address the research question: What is the current cybercrime capacity and capability of local law enforcement agencies in the United States? Findings from this project advance our knowledge about the cybercrime capacity and capability of local law enforcement agencies and contribute to strengthening law enforcement practice, policy, and future research. In total, 925 county and municipal agencies participated in this research project through a survey instrument called the Cybercrime Capacity and Capability Questionnaire (CCCQ©), with 855 agencies providing data usable for analysis. Additionally, 23 individuals representing 23 distinct agencies, who previously participated in the CCCQ, also participated in a series of semi-structured qualitative interviews. Multiple findings and recommendations were derived as a result of the participation by these agencies and individuals in this project. Several findings from this project aligned with or validated findings and recommendations from other recent studies (for example Harkin et al., 2018). Among the key findings from this project are that the cybercrime capacity and capability of local law enforcement agencies is deficient, despite trends at the local law enforcement agency level to allocate more resources to the cybercrime problem. This deficiency is noted both by response patterns on the CCCQ© and through comments supplied during the qualitative interviews. Lack of financial and personnel resources, especially technologically skilled and competent personnel, limited and/or outdated technological infrastructure, and problems leveraging partnerships and obtaining cooperation from private sector organizations are just a few of the challenges hampering the development of a more robust local law enforcement cybercrime capacity and capability. Results and insights from this research also illuminate the dynamic process of developing cybercrime capacity and capability. Result from this project indicate that caution should be exercised before assuming that cybercrime capacity and capability are solely a function of agency size. While this project substantiates other research that shows larger agencies are more likely to have cybercrime units, and also tend to have more resources, personnel, and equipment for cybercrime investigations, they do not necessarily have greater cybercrime capacity or capability. Cybercrime case volume appears to impact cybercrime capacity and capability such that large local law enforcement agencies, despite specialized cybercrime units and more resources allocated to cybercrime, may not be better off in managing cybercrime incidents or responding to cybercrime related issues than midsize and smaller local agencies. Personnel at larger agencies, despite having dedicated cybercrime units, more resources, and better equipment, may be at higher risk of burnout and other issues as a result. In short, extremely high cybercrime case volumes may undermine the capacity and capability of even the most robustly developed specialized cybercrime units, as well as the best equipped and resourced agencies. Given the pace at which the cybercrime problem is growing, this is a troubling finding. This project also highlights that cybercrime capacity and capability cannot be understood without accounting for the critical differences that external forces and contextual factors produce on local law enforcement agencies that, in turn, impact how those agencies function and adapt to new issues and challenges. For example, qualitative data from this project help us to understand the connections between the defund the police movement and the COVID-19 pandemic, both of which appear to be undermining the capacity and capability of local law enforcement agencies, and thus negatively impacting their cybercrime capacity and capability. As a result, cybercrime administrators and personnel at local law enforcement agencies in the U.S. may be experiencing similar challenges to their peers abroad (see Harkin et al. 2018). A number of directions for future research, improvement of the CCCQ©, and recommendations for improving police practice and policy such as developing uniform, and operationalizable cybercrime best practices and strengthening private sector compliance with law enforcement agency requests for data are also provided.